A Reader's Guide to William Faulkner : The Short Stories - Volpe, Edmond Loris (Book collections on Project MUSE., 2004)
This Guide offers analyses of all Faulkner's short stories, published and unpublished, that were not incorporated into novels or turned into chapters of a novel. Each of the seventy-one stories receives separate and detailed appraisal. This approach helps establish the relationship of the stories to the novels and underscores Faulkner's skill as a writer of short fiction. Although Faulkner often spoke disparagingly of the short story form and claimed that he wrote stories for money, which he did, this critical study reveals that Faulkner could not resist the application of his creative imagination or his mastery of narrative structure and technique to this genre. -- From back cover.